Governmental support for social responsibility in small and medium-sized enterprises - Buhr, Katarina; Hermansson, Anna (2004)
Several European governments have pointed out corporate social responsibility (CSR) as a deliberate strategic area with potential to enhance the national competitiveness on sustainable terms. CSR can be understood as a contribution by the private sector to sustainable development. In this paper, CSR will be referred to as social responsibility when small and medium-sized enterprises (SMEs) are in focus of the discussion, since the word "corporate" often is associated with larger companies. From a national as well as an international perspective, it is crucial to include SMEs in the expanding work with CSR to ensure that it spreads among all sections in business, which is likely to lead to positive effects on society. Each government has an opportunity to influence the country's future direction of CSR through political means of control and the work on developing effective support measures. This paper contributes to the understanding of how the CSR message is handled and communicated by governments in different countries due to the complexity and the politics involved. It provides an overall picture of Sweden's and the Untied Kingdom's governmental support for social responsibility in SMEs and put them into comparison. Two opposite trends can explain the practical differences, but also points of similarities, that exist in European countries. One trend is the national context that sets the preconditions for each country's work on CSR and is counteracting the other trend which is the creation of an international framework for CSR that aims to harmonize the countries' procedures. The main findings are that CSR appears to be managed more strategically within the UK government compared to the Swedish government and that it has a profound effect on the way that the support measures for SMEs are designed. The United Kingdom offers a holistic approach to the CSR concept to a greater extent than Sweden where it is more common to focus on specific areas within CSR. Sweden primary focus on sustainable development in all parts of society whereas the United Kingdom points out the potential of business' voluntary activities as a major contribution to sustainable development. One explanation for this can be found in the fact that the UK government relies on the private and voluntary sector to a greater extent than the Swedish government.